Work Motivation Influence On Performance Officer at Kantor Pelayanan Perbendaharaan Negara (KPPN) Pontianak - B11106091, SITI HAJIJAH (Jurnal Manajemen Update, 2013)
Employees are social beings who became an important asset for any company/ organization,they become planners, implementers, and the controllers are always played an active role in realizing the goal of an organization is there for the management of the organizationmust understand their employees well and can create employee satisfaction. This study aims to determine how employee job satisfaction Kantor Pelayanan Perbendaharaan Negara (KPPN) Pontianak. This study uses a qualitative analysis using a questionnaire which collected data classified as tabulated and presented in tabular form then just concluded. Based on the analysis conducted, it can be concluded that the variables that influence employee job satisfaction are fringe benefits, job placement, light weight work,atmosphere and working environment, tools that support the execution of the work,attitude and leadership led the monotonous nature of the job or not.Where there is still a lack of appropriate variables (less than satisfactory) that the equipment is inadequate to support the implementation of the work, so the job is often not completed exactly at the specified time.